Airborne β-caryophyllene disrupts virus–vector mutualism by priming tomato defenses - Peng-Jun Zhang; Rui-Chen Li; Ye-Hua Li; Hong-Jian Wan; Da-Wei Xue; Bao-Li Qiu; Ted C. J. Turlings (Proceedings of the National Academy of Sciences, 2026)
Whiteflies pose a major threat to crops worldwide, primarily because they transmit begomoviruses with which they have evolved intricate mutualistic relationships. The mutualisms are known to exacerbate whitefly invasions and drive widespread plant virus pandemics. Yet, certain plant genotypes are able to resist both the whiteflies and the viruses and a good understanding of the underlying mechanisms could help to develop more resistant varieties. Here, we show that the viruliferous whitefly Bemisia tabaci induces an early and strong release of the sesquiterpene β-caryophyllene in cultivated tomato plants. This volatile functions as an airborne signal that primes neighboring conspecifics for enhanced resistance to begomoviruses, including Tomato yellow leaf curl virus and Papaya leaf curl China virus. These results challenge the view that whitefly-induced volatile emissions primarily benefit the insect vector, suggesting instead that the plant prioritizes antiviral defense over antiherbivore resistance. β-Caryophyllene exposure was also found to enhance the emission of β-Caryophyllene, methyl salicylate and β-myrcene upon whitefly attack, increasing plant attractiveness to the parasitoid Encarsia formosa . Using a β-caryophyllene overproducing transgenic tomato line and synthetic β-caryophyllene dispensers, we confirmed that β-caryophyllene exposure primes antipathogen defenses in tomato plants and confers improved plant fitness under sustained infestation by viruliferous whiteflies. Importantly, this defense priming is genotype-specific and limited to certain tomato cultivars, suggesting that β-caryophyllene-mediated resistance can be harnessed through selective breeding. Our findings reveal a volatile-based mechanism by which tomato plants may counteract the virus–vector mutualism, offering promising avenues for integrated pest and disease management.